2016
DOI: 10.4236/aim.2016.64027
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Curcumin-Treated Herpes Simplex Virus 1 and 2 in Vero Cells

Abstract: The purpose of this study was to investigate the effect of curcumin-treated Herpes simplex virus-1 (HSV-1) and Herpes simplex virus-2 (HSV-2) virions in cultured Vero cells. Previous studies have indicated that curcumin, a polyphenol extracted from the plant Curcuma longa, has demonstrated antiviral properties against a variety of viruses. After establishing the maximum non-cytotoxic concentrations of curcumin on Vero cells, HSV-1 and HSV-2 virions were treated with varying concentrations of curcumin. The effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 39 publications
2
18
0
Order By: Relevance
“…Several natural compounds have been investigated as potential therapies. These natural products include eucalyptus extracts [34], polysaccharides and diglycerides [35], curcumin [36], and polyphenols from tea [24] Herpes simplex virus infections continue to affect a large percentage of the human population worldwide. There is no cure for HSV-1 infections and there remains a need to identify effective and affordable therapies to reduce the incidence.…”
Section: Discussionmentioning
confidence: 99%
“…Several natural compounds have been investigated as potential therapies. These natural products include eucalyptus extracts [34], polysaccharides and diglycerides [35], curcumin [36], and polyphenols from tea [24] Herpes simplex virus infections continue to affect a large percentage of the human population worldwide. There is no cure for HSV-1 infections and there remains a need to identify effective and affordable therapies to reduce the incidence.…”
Section: Discussionmentioning
confidence: 99%
“…The cells tolerated up to 15 μg/mL and 60 μg/mL curcumin and Cur-CS nanoparticles, respectively. The cytotoxic effect of curcumin on different cells has been well demonstrated, where no cytotoxic effect was observed following exposure up to 30 μM curcumin [19,60,61]. The MTT results of the present study revealed that the Cur-CS nanoparticles had less cytotoxic effects than curcumin in a dose-and time-dependent Table 4, significant protective effects were observed in each stage; however, 20 μM curcumin and Cur-CS nanoparticles showed the highest protection percentage in cotreatment at 48 h, namely, 56% and 68%, respectively.…”
Section: Stability Studymentioning
confidence: 99%
“…Herpes simplex virus (HSV) is a highly contagious and endemic pathogen that causes herpes labialis, herpes genitalis, encephalitis, and keratitis [1]. HS viral infections are considered to be a significant health problem worldwide [2]. The HSV infection caused by both type 1 (HS-1) and type 2 (HS-2) viruses could be transmitted through close personal contact [3].…”
Section: Introductionmentioning
confidence: 99%
“…Turmeric (Curcuma longa Linn) is generally recognized as safe (GRAS) by the FDA [6] and is extensively used as a folk medicine for its antioxidant, anti-inflammatory, and antiseptic effects, particularly in Asian countries [7]. Curcumin (1,7-bis(4-hydroxy-3-methoxyphenyl)-1,6-heptadiene-3,5-dione) is the main curcuminoid derived from turmeric rhizomes [2,8]. The therapeutic efficacy and safety of curcumin (up to 12 g/day) make it an attractive target for the prevention and treatment of different human diseases [9].…”
Section: Introductionmentioning
confidence: 99%